(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The aim of this study was to determine the Diagnostic Accuracy of Doppler sonography for the diagnosis of Resistive Index of ovarian carcinoma taking histopathology as gold standard. Methods: Fifty patients with complex pelvic masses assessed preoperatively with two-dimensional ultrasound (2DUS), two-dimensional power Doppler (2DPD), color Doppler taking histopathology as gold standard. Results: All patients underwent exploration, 11 (22%) had other lesions, 39 (78%) had ovarian cancer. 2DUS with 2DPD & Color Doppler RI of 0.4 identified 39 cases, suggests these patients had ovarian tumour giving 92.6 % sensitivity, 88.8 % specificity , 97.4 % positive predictive value, 72.73 % negative predictive value and 92.0 % diagnostic accuracy. Conclusion: Evaluation by power Doppler ultrasound improves diagnostic accuracy of ovarian tumors. We strongly recommend Doppler Sonography for the evaluation of ovarian carcinoma because it is highly accurate, easily available and non-invasive imaging modality for its diagnosis.